2017
DOI: 10.3989/scimar.04597.18a
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomic assessment of a change in fishing gear selectivity: the case of a single-species fleet affected by the landing obligation

Abstract: Summary:The European Union Common Fisheries Policy has established a discard ban, which states that fish below a reference size cannot be sold directly for human consumption. In a fishing effort-regulated fishery, the discard ban can result in extra handling, storing and landing costs. In an output-regulated fishery, this policy might also limit the effort levels as all the catches count against the quota. In both cases, this regulation can reduce the economic performance of the companies, even in single-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Colloca et al (2014) recommended changes in the selectivity patterns to decrease fishing mortality and delay the age at first capture as a more practical and efficient way to recover Mediterranean fish stocks than mere effort-reduction measures. Additionally, in light of the current Common Fisheries Policy, in which a ban of discards on regulated species can provide additional incentives for improving fisheries selectivity (Prellezo et al 2016(Prellezo et al , 2017, our results show that it is possible to reduce fishing mortality and contribute to stock rebuilding by relatively simple, inexpensive modifications to trawl nets that enhance size selectivity.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Colloca et al (2014) recommended changes in the selectivity patterns to decrease fishing mortality and delay the age at first capture as a more practical and efficient way to recover Mediterranean fish stocks than mere effort-reduction measures. Additionally, in light of the current Common Fisheries Policy, in which a ban of discards on regulated species can provide additional incentives for improving fisheries selectivity (Prellezo et al 2016(Prellezo et al , 2017, our results show that it is possible to reduce fishing mortality and contribute to stock rebuilding by relatively simple, inexpensive modifications to trawl nets that enhance size selectivity.…”
Section: Discussionmentioning
confidence: 75%
“…Selectivity improvements inevitably have short-term negative consequences for the fisheries operators' profitability, and consequently a low incentive for adoption, but will in the long term help rebuild stocks and produce higher yields, particularly in heavily overexploited resources such as Mediterranean stocks (Colloca et al 2014). On the other hand, the analysis of the Basque trawl fishery in the Bay of Biscay by Prellezo et al (2016Prellezo et al ( , 2017 showed that private incentives can arise to improve the selectivity and reduce discards through the adoption of more selective fishing gear by fishers as a logical outcome of the LO, on bioeconomic grounds only. Naturally, any modifications to the current trawl design should be practical and inexpensive to facilitate its wide and fast adoption by fishers.…”
Section: Introductionmentioning
confidence: 99%
“…Dashed lines indicates the FMSY level and SSBlim (computed as SSBlim = 1.4*SSBmin, where SSBmin is the minimum value of SSB observed in the historical data series). Gullestad et al, 2015;Sardà et al, 2015;Prellezo et al, 2017). Moreover, improving selectivity would modify reference points and decrease the current levels of fishing mortality on F MSY (Scott and Sampson, 2011).…”
Section: Figure 12 |mentioning
confidence: 99%
“…To comply with these constraints, fishers' interests are to reduce bycatch (i.e., unwanted catch) through more selective fishing practices. The development of selective fishing gears is extensively studied (Alzorriz et al, 2016;Batsleer et al, 2016;Mortensen et al, 2017;Prellezo et al, 2017;Kopp et al, 2018), but it requires time, important financial resources and is hardly achieved in mixed-fisheries (Suuronen and Sardà, 2007;Catchpole et al, 2008;Romero et al, 2010). Another possibly complementary approach consists in allocating fishing effort to other species, fishing grounds or seasons to avoid bycatch (e.g., Batsleer et al, 2013;Branch and Hilborn, 2008;Simons et al, 2015).…”
Section: Introductionmentioning
confidence: 99%